Endocannabinoid signalling in atherosclerosis and related metabolic complications - Guillamat-Prats, Raquel; Herzig, Stephan (Thrombosis and haemostasis, 2019)
Endocannabinoids are a group of arachidonic acid-derived lipid mediators binding to cannabinoid receptors CB1 and CB2. An overactivity of the endocannabinoid system plays a pathophysiological role in the development of visceral obesity and insulin resistance. Moreover, elevated circulating endocannabinoid levels are also prevalent in atherosclerosis. The pathophysiological increase of endocannabinoid levels is due to an altered expression of endocannabinoid synthesizing and degrading enzymes induced by inflammatory mediators such as cytokines or lipids. Emerging experimental evidence suggests that enhanced endocannabinoid signalling affects atherosclerosis via multiple effects, including a modulation of vascular inflammation, leukocyte recruitment, macrophage cholesterol metabolism and consequently atherosclerotic plaque stability. In addition, recent findings in various metabolic disease models highlight the relevance of peripheral CB1 cannabinoid receptors in adipose tissue, liver and pancreas, which crucially regulate lipid and glucose metabolism as well as macrophage properties in these organs. This suggests that targeting the endocannabinoid system in the vasculature and peripheral organs might have a therapeutic potential for atherosclerosis by inhibiting vascular inflammation and improving metabolic risk factors. This review will provide a brief update on the effects of endocannabinoid signalling in atherosclerosis and related metabolic complications.
Gesehen am 29.01.2020